Ethnocultural technology in musical and pedagogical training of students of pedagogical universities of China - Tingting, Zhang (Edelweiss Applied Science and Technology, 2025)
This study aims to develop and implement an ethnocultural technology that integrates Chinese traditional artistic practices into the musical and pedagogical training of students majoring in vocal music at pedagogical universities. The technology incorporates methods such as Gundoku (expressive group recitation), melodeclamation (poetic recitation with musical accompaniment), and the Mei Lanfang gesture system, all rooted in Chinese opera traditions. An experimental study was conducted with 84 fourth-year students at Changchun Humanities and Sciences College, China, during the 2020–2021 academic year. Results showed significant improvements in students’ stage performance skills, vocal clarity, expressive movement, and pedagogical competencies, such as conducting choral groups and using expressive speech in teaching. The technology effectively bridges performance training with pedagogical application, enhancing both artistic and teaching capabilities. These findings suggest that ethnocultural methods can enrich music teacher education, with implications for curriculum design and intercultural music pedagogy.